Fulminant Guillain-Barré Syndrome Post Hemorrhagic Stroke: Two Case Reports - Sameeh Abdulmana; Naif Al-Zahrani; Yahya Sharahely; Shahid Bashir; Talal M. Al-Harbi (MDPI AG, 2021)
Guillain-Barré syndrome (GBS) is an acute, immune-mediated inflammatory peripheral polyneuropathy characterized by ascending paralysis. Most GBS cases follow gastrointestinal or chest infections. Some patients have been reported either following or concomitant with head trauma, neurosurgical procedures, and rarely hemorrhagic stroke. The exact pathogenesis is not entirely understood. However, blood-brain barrier damage may play an essential role in triggering the autoimmune activation that leads to post-stroke GBS. Here, we present two cases of fulminant GBS following hemorrhagic stroke to remind clinicians to be aware of this rare treatable complication if a stroke patient develops unexplainable flaccid paralysis with or without respiratory distress.